AHAMEFULA GENDER COMPLEMENTARITY IN LEADERSHIP: A CASE FOR GENDEROCRACY - Ephraim Ahamefula Ikegbu (Universitas PGRI Madiun, 2022)
Most developing and third world countries are deeply engrossed with patrilineal form of leadership which is male-dominated. Any system of government that does not accommodate all segments of the society cannot be seen to be globally accepted especially in this age of consciousness on human rights, justice and rule of law. This paper